Perspectives of Women Giving Birth in Zambia - Concepta Kwaleyela; Sheila Greatrex-White; Walsh Denis (Mashhad University of Medical Sciences, 2019)
Background & aim: Women experience childbirth in a variety of contexts with different aspirations. However, the experience has far-reaching implications for women's health and that of their neonates. To explore the childbirth experiences of women giving birth in Zambia in order to better understand how they give meaning to the experience this study was conducted. Methods: This study was carried out using an interpretive phenomenological approach. Purposive sampling was utilized to recruit 50 participants from all the 10 provinces of Zambia. The ages of the subjects ranged from 16 to 38 years. The deliveries, both home and institutional, occurred between 2005 and 2011. The data were collected through tape-recorded in-depth unstructured interviews. Data analysis was performed using van Manen's six steps of analysis. Results: The major theme of "being there" constituted two subthemes, namely "feeling safe" and "sense of achievement" emerged from the obtained data. The major theme elucidated the physical presence of the provider, as well as feelings of safety, comfort, trust, being recognized, and respected. The subtheme of "feeling safe" explicated women's feelings of being at ease and at peace with their care providers, while the subtheme of "sense of achievement" clarified the participants' expressions of pride that came through experiencing childbirth perceived by the woman giving birth to be satisfactory.  Conclusion: By being physically and psychologically present for the woman who is giving birth, birth attendants, particularly midwives assisted in raising their confidence levels. Caring behaviours, such as showing kindness and respect, giving privacy, as well as making the cases feel comfortable made a qualitative difference of the childbirth experience.